Forensic analysis: Crimes against the sexual freedom of children and vulnerable persons (Research, Society and Development, 2025)
Delitos Sexuales is any unwanted sexual act committed by any person, regardless of their relationship with the victim or the setting in which it occurs. Within the scope of forensic analysis, the application of chemical, psychological, neuropsychological, physical, and laboratory evaluations are crucial steps in the forensic process and serve as major tools in the creation of the expert report. Sexual violence against children and vulnerable individuals causes irreversible harm and trauma to its victims.This study aims to define how forensic evaluation is conducted and to identify its use in cases of sexual abuse against children and vulnerable individuals. In light of the need to understand the procedures used to close cases of child and vulnerable sexual violence, forensic analysis emerges as a key element in resolving these crimes, as well as in understanding the stories behind each case. The main objective consists of an analysis of and understand in an efficient methodological manner in the diagnosis and resolution of cases of sexual violence committed against youth, children, and vulnerable persons. Providing information to girls helps in the fight against violence:"The generation of girls, adolescents, and young women is more informed."The sexological examination, carried out by a forensic physician, consists of examining the body—especially the victim's genitals—to determine whether a sexual assault occurred. This study will utilize databases of scientific articles, including: Scientific Electronic Library Online (SCIELO), Virtual Health Library (BVS), National Library of Medicine (PUBMED), and Google Scholar. We aim to highlight the difficulties encountered both within the family sphere and in the provision of support by technical teams.